Rekayasa Sistem MONEV Proses Belajar Mengajar di STMIK Lombok - Hamdani, Zainal Basit; Zaen, Mohammad Taufan Asri; Fahmi, Hairul; Ashari, Maulana (Jurnal Ilmiah Teknik Mesin, Elektro dan Komputer, 2023)
Monitoring activities for the teaching and learning process at STMIK Lombok are currently not fully operational, causing various violations and omissions committed by lecturers and students not known by superiors who should be obligated to carry out this monitoring. Some examples of violations and omissions found were students and lecturers being late for lectures, lectures being held not according to a predetermined schedule, students and lecturers filling out lecture attendance that they did not attend, late submission of lecture documents conducted by lecturers, and lectures not being given in accordance lecturers with lesson plans and syllabus that have been prepared. The process of evaluating lecturer performance is carried out at the end of each semester based on the results of the questionnaire filled in by each student. However, the results of this evaluation are considered to be ineffective because they are still subjective, requiring additional data that is more accurate and measurable so that Management will find it easier to determine what actions need to be taken to improve and develop the quality of education at STMIK Lombok. To deal with the problems, the researchers designed an information system for monitoring and evaluating the teaching and learning process at STMIK Lombok. The analytical method used in this study is PIECES, while the design method used is waterfall, and for testing it uses the Blackbox method. The results in this study are websites built with the PHP programming language using the Laravel Framework and for the database used, namely MySQL. In this system there are 6 types of users that are distinguished according to their respective roles and each role has different access rights. The system is integrated with the system and database of SIAKAD STMIK Lombok. Several monitoring and evaluation units that are processed by the system are lecture documents such as lesson plans, syllabus, grades and student attendance, as well as assessment questionnaires and feedback from students on lectures given by lecturers.